2020
DOI: 10.1167/iovs.61.11.28
|View full text |Cite
|
Sign up to set email alerts
|

The Fovea in Retinopathy of Prematurity

Abstract: Purpose Because preterm birth and retinopathy of prematurity (ROP) are associated with poor visual acuity (VA) and altered foveal development, we evaluated relationships among the central retinal photoreceptors, postreceptor retinal neurons, overlying fovea, and VA in ROP. Methods We obtained optical coherence tomograms (OCTs) in preterm born subjects with no history of ROP (none; n = 61), ROP that resolved spontaneously without treatment (mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 41 publications
3
19
0
1
Order By: Relevance
“…The present study may have clinical significance for both children and adults: In previous reports in children, 2 adolescents and early adulthood, 45 as well as the EPICure@19Study 21 investigating subjects up to 19 years of age, a correlation between retinal layer thickness in the macula region with best corrected visual acuity was observed. Consequently, one may speculate that an altered foveal shape may lead to an increased risk for reduced visual acuity in life, or that this is not necessarily associated with reduced visual acuity, as increased foveolar thickness in former preterm newborns only indicates former prematurity or prenatal growth restriction.…”
Section: Discussionsupporting
confidence: 57%
“…The present study may have clinical significance for both children and adults: In previous reports in children, 2 adolescents and early adulthood, 45 as well as the EPICure@19Study 21 investigating subjects up to 19 years of age, a correlation between retinal layer thickness in the macula region with best corrected visual acuity was observed. Consequently, one may speculate that an altered foveal shape may lead to an increased risk for reduced visual acuity in life, or that this is not necessarily associated with reduced visual acuity, as increased foveolar thickness in former preterm newborns only indicates former prematurity or prenatal growth restriction.…”
Section: Discussionsupporting
confidence: 57%
“…Prior OCT studies in children and young adults with a history of prematurity or ROP treatment demonstrated abnormal anatomical foveal structures, including the persistent presence of the inner retina at the fovea center, and a shallower foveal pit, 9 16 , 25 suggesting that prematurity or the combination of prematurity and ROP treatment interferes with normal foveal pit maturation. Our study revealed that the foveal inner retina was thicker in EPT infants throughout the observation period (phases 1–3) when compared with non-EPT infants and negatively correlated with PMA ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that prematurity and ROP both alter foveal development, which has been associated with abnormalities that include an inability to displace inner retinal layers away from the fovea, causing thickening of the fovea that persisting into childhood and adulthood. 9 16 Advancements in optical coherence tomography (OCT) acquisition has allowed for the visualization of the fovea in supine infants, thus providing an opportunity to refine our understanding of foveal development. Therefore, the purpose of this study was to investigate OCT features that occur in foveal development during the postnatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Applying this analysis, studies in healthy populations discovered important racial and sex differences in foveal pit morphology [19][20][21][22]. Additionally, some studies investigated differences in the fovea of patients with Parkinson's disease [23][24][25], foveal retinopathy [26] and neuromyelitis optica spectrum disorders [27]. Now that foveal pit morphology analysis is gaining attention it is important to establish a solid foundation for its methodology.…”
Section: Introductionmentioning
confidence: 99%